Maximize Profit by Implementing Inventory Management in Construction Industry - Leong, Hui Shan (2020)
Construction inventory management is essential for construction projects to maximize the company's profit. Material costs account for 50% to 60% of the total project cost therefore a good control of project inventory can increase project profits. Effective inventory management can increase project efficiency because materials are available when needed. However, ineffective inventory management is still a common problem in the Malaysian construction industry. Ineffective inventory management can cause project delays and fail to meet client requirements. Construction companies not only face losses but also create a bad reputation for the company. Although advanced inventory technologies such as radio frequency identification (RFID) or smart tags have been introduced into the construction industry to improve the efficiency of inventory management. However, for some reasons, most Malaysian construction companies still refuse to adopt advanced inventory technology, especially small and medium sized construction companies. Most small and medium construction companies still rely on inventory techniques to manage their project inventory, such as ABC analysis, EOQ analysis and S-curve. Inventory techniques have greatly related to inventory management because inventory techniques will affect the efficiency of inventory management. The wise use of inventory techniques can also significantly improve project inventory management. Therefore, the aim of this research is to explore an effective inventory management system to maximize the profit of the construction company. In this study, the factors leading to ineffective inventory management will also be determined. In addition, this research will also study various types of inventory management techniques and the effectiveness of using inventory management techniques on projects to maximize profits. Literature review and questionnaire survey were conducted to obtain data for this research. Data analysis will involve the mean score calculation. The research will benefit construction parties who intend to improve or adopt inventory management techniques to maximize company profits.